Problems in Evaluating the Effectiveness of Sales Promotion Activities - Brar, Vinaydeep; Kumar, Atul; Ramgade, Atul (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Organisations spend substantial amounts on sales promotion of goods and services. They ought to know the effectiveness of the sales promotion activities. To evaluate this effectiveness, different metrics are used. These include profits, return on investment, sales volume, pull-forward, halo, cannibalisation, engagement of old customers, customer satisfaction, and others. Easier said than done, evaluating the effectiveness of sales promotion activities can be a complicated task in practice, especially if there are multiple products involved. Allocation of revenue and costs over products and periods can be complex. There might be expected costs, and the division of such expenses can pose problems. A suitable basis needs to be developed for the allocation. In this paper, we present the practical difficulties involved in evaluating the effectiveness of sales promotion activities based on a survey of 110 marketing managers working in large MNCs from Pune. Findings suggest that multiple issues crop up in the actual evaluation, and at times, some approximation goes into the exercise of assessment.